The Importance of Business Travel for Trade: Evidence from the Liberalization of the Soviet Airspace - Bengt Söderlund (Research Institute of Industrial Economics (IFN), 2020)
The strong negative relationship between geographical distance and trade is not well understood. I use the liberalization of the Soviet airspace to estimate the causal impact of business travel cost on trade. The liberalization radically reduced travel time between Europe and East Asia and was associated with a significant increase in trade. I find that the cost of business travel can account for most of the trade frictions (85.3%) that cause trade to sharply decline with distance. A plausible explanation for these results is that face-to-face interaction through business travel is important for trade, and that transporting people is costly.
Keywords: F14; F15; R40; 330; Trade costs; Air travel; Face-to-face communication